Five ultimate tips of writing catchy titles: which one is your favourite? - Harun, Nur Syikri; Ismail, Fathiyah; Abdul Samad, Nor Zaitolakma (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
Do you know how to grab readers’ attention to read articles you write? Don’t you think that it's essential to gain their interest to enjoy your masterpieces? How to make them stand out? Is it effortless to write ones? Well! Writing the whole essay is one topic, but writing a title of the article is quite another. This is because an article is meant to be read not only by its author per se but other readers, too. It serves as a warm, assiduous, and earnest host welcoming his or her guests to a house where a party is being thrown at. Powell (2021) has visualised the beauty of writing engaging titles as equally important as their contents. David Ogilvy, a British advertising tycoon popular for highlighting creative copy and themes on campaigns has once said that “on the average, five times as many people read the headline as read the body copy. When you have written your headline, you have spent eighty cents out of your dollar”. Raymond Chandler has also opined that “a good title is the title of a successful book”.